CFOs versus CEOs: Equity incentives and crashes - KIM, Jeong-Bon (Institutional Knowledge at Singapore Management University, 2011)
Using a large sample of U.S. firms for the period 1993-2009, we provide evidence that the sensitivity of a chief financial officer's (CFO) option portfolio value to stock price is significantly and positively related to the firm's future stock price crash risk. In contrast, we find only weak evidence of the positive impact of chief executive officer option sensitivity on crash risk. Finally, we find that the link between CFO option sensitivity and crash risk is more pronounced for firms in non-competitive industries and those with a high level of financial leverage.